Fibre optic humidity and pH sensing for healthcare and sports applications - Gomez, David (2019)
The ultimate objective of this PhD thesis is the development and characterisation of optical fibre sensors for humidity and pH monitoring with the aim of exploring their applications in healthcare and sport. In particular, wound healing monitoring, foetal blood sampling and body sweat rate during exercise were explored. Sensors have been thoroughly characterised to establish key parameters such as sensitivity, response time, cross sensitivity to temperature, wearability and portability of the sensors.